1991
DOI: 10.1116/1.577431
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of amorphous SiC:H thin films

Abstract: Silicon carbide films were deposited by plasma enhanced chemical vapor deposition utilizing monomethylsilane (CH3SiH3). Silicon (100) and polycrystalline gold were used as substrates. A mass spectrometric analysis of the monomethylsilane plasma showed that the majority of the Si–C bonds were preserved in the gas phase. The composition, the density and morphology of the amorphous SiC:H (a:SiC:H) films were studied as a function of substrate temperature, composition of the ion flux bombarding the surface and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 5 publications
(5 reference statements)
4
38
1
Order By: Relevance
“…and T650_OX were very close at around 0.88. All the films are carbon rich, contrary to what was reported by other groups [15,16], demonstrating that film composition is process dependent, though the same precursor MS was used. The oxygen atomic concentration in a-SiC deposited on Si substrate was higher than that deposited on oxide covered Si substrate at constant deposition conditions and the difference was minimized with increasing deposition temperature.…”
Section: Dependence Of Chemical Composition On Deposition Temperaturecontrasting
confidence: 81%
See 2 more Smart Citations
“…and T650_OX were very close at around 0.88. All the films are carbon rich, contrary to what was reported by other groups [15,16], demonstrating that film composition is process dependent, though the same precursor MS was used. The oxygen atomic concentration in a-SiC deposited on Si substrate was higher than that deposited on oxide covered Si substrate at constant deposition conditions and the difference was minimized with increasing deposition temperature.…”
Section: Dependence Of Chemical Composition On Deposition Temperaturecontrasting
confidence: 81%
“…The incorporation of H 2 during the deposition can either widen or narrow the optical energy gap of deposited SiC films [17][18][19]. The composition and chemical bonds of a-SiC prepared from MS had been reported [15,16], however, the employed deposition method was plasma enhanced chemical vapour deposition (PECVD) rather than standard low-pressure chemical vapour deposition (LPCVD). In this paper, the deposition of a-SiC is performed using MS as a single precursor (without dilution gas) in a standard LPCVD reactor at medium deposition temperatures, and the aim is to investigate the dependence of chemical composition and bonding of a-SiC on deposition temperature and the choice of substrate.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…2c) in the diffusion layer: one with BE of 100.29 eV is bonded with C element and labeled as "Si C 2p". Delplancke et al [28] have found that the binding energy of Si2p in SiC 1.3 , SiC 1.5 and SiC 1.7 is about 100.10À 100.30 eV by XPS. The other one with BE of 98.98 eV is bonded with O element and labeled as "Si O 2p", which is in agreement with other results (98.70À98.90 eV) [29].…”
Section: Resultsmentioning
confidence: 99%
“…Since, SiC is the main barrier for gaseous and metallic fission product release. However, recent literatures 112 reveal that the formation of different isotopes of Si on the SiC crystal structure 113 during the CVD 47 Ar-Plasma CVD RT, exposure to HCl to 1073 K (a-SiC) 48 ULP-CVD LT SiC(001) 49 CVD RT and H 2 annealing (a-SiC) 50 HW-CVD 1073 K (polycrystalline-SiC) 48 Filament temperature: 2273 K; T s 5 573 K; 75 Pa (b-SiC) 51 HW-CVD 1873; 573 K (b-SiC) 52 LPCVD and PECVD 1023 K (a-SiC) 53 92 1,3-disilabutane HVCVD 723-1423 K; ,3 Â 10 À7 mbar (b-SiC) 93 1,3-disilabutane CVD 1073-1273 K; 10 À4 and 10 À5 Torr (b-SiC) 94 1,4-bis(trimethylsilyl)benzene PECVD 573 K (a-SiC) 95 Silacyclobutane LPCVD 1073-1473 K 96 1, manufacturing process and after transmutation due to irradiation may affect the integrity of the SiC layer. Among them, when 28 Si or 29 Si atoms absorb a thermal neutron, they are changed into other stable silicon atoms.…”
Section: Desired Structure Of Sic For Nuclear Applicationsmentioning
confidence: 99%